2020
DOI: 10.1155/2020/9490807
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Rock Crack Propagation Induced by Blasting with a Decoupled Charge under High In Situ Stress

Abstract: The high in situ stress can significantly affect the blast-induced rock fragmentation and cause difficulties in deep mining and civil engineering where the drilling and blasting technique is applied. In this study, the rock crack propagation induced by blasting under in situ stress is first analyzed theoretically, and then a numerical model with a decoupled charge in LS-DYNA is developed to reveal how the initiation and propagation of rock cracks are under high in situ stress. Through simulation, the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…To dismantle with a small amount of SPC agent, it is better to propagate the crack flatly using intragranular fracturing to control the crack; the crack can easily stop the resistance by breaking the grain boundaries. Whether cracks penetrate the aggregate or propagate along the boundary is an important problem for future research and requires theoretical analysis [ 25 , 26 , 27 ]. In the future, an appropriate strength should be achieved at the interface surface, and concrete with high strength and easy fracture control is desired.…”
Section: Resultsmentioning
confidence: 99%
“…To dismantle with a small amount of SPC agent, it is better to propagate the crack flatly using intragranular fracturing to control the crack; the crack can easily stop the resistance by breaking the grain boundaries. Whether cracks penetrate the aggregate or propagate along the boundary is an important problem for future research and requires theoretical analysis [ 25 , 26 , 27 ]. In the future, an appropriate strength should be achieved at the interface surface, and concrete with high strength and easy fracture control is desired.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they proved that brittleness is an inherent physical property that affects material crushing. Li et al [31] revealed the initiation and propagation processes of rock cracks under elevated in situ stresses and discussed the mechanism of blasting-induced crack evolution under different hydrostatic and nonhydrostatic pressures. Yang et al [32] studied rock damage under the action of in situ stresses and the changes in critical peak particle velocity (PPV) and stress release time.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of the lateral pressure coefficient, the extending direction of the tensile damage zone becomes more obvious, which causes a great challenge to the cutting blasting excavation in deep rock masses. Yi, Jayasinghe, Ma and Li [15][16][17][18] used LS-DYNA to investigate the influence of in situ stress on the blast-induced cracks. Their results showed that the crack propagation trends towards the direction of maximum compressive pressure.…”
Section: Introductionmentioning
confidence: 99%